RICE: a market description - Nery, Iane Beatriz Damasio; Cella, Daltro (Revista Interface Tecnológica, 2022)
Rice (Oryza sativa) was introduced in Brazil in 1530 by Pedro Álvares Cabral's convoy in the Captaincy of São Vicente. The expansion of production took place first on the coast and later to the interior of Brazil with pastures and coffee cultivation. It is the second most produced and consumed cereal in the world, after wheat. This research aimed to survey the production and market of rice. In order to understand the rice market, theoretical and quantitative research were carried out to order and classify the countries participating in this market. Rice cultivation occurs mainly in populous and low-income countries. In Brazil, production is concentrated in the southern region, which is responsible for more than 82% of production. In 2020, world stocks were 37% of world consumption needs. China dominated the rice market, as the largest producer and importer; seventh largest exporter; and, with an annual per capita consumption above 100 kg. Brazil was the 9th largest producer, 10th largest exporter, 18th largest importer. The main buyers of Brazilian rice were Venezuela (20.6%) and Peru (12.1%). Most of Brazil's rice imports were from Mercosur countries. The per capita consumption of processed rice in Brazil in 2022 was 33.1 kg. Rice is an affordable product for low-income workers, and any change in consumption or supply can lead to imbalances in market prices.
Keywords: Rice.; Commercialization.; Production.; Import.; Export.